PENGARUH JARAK KEKUASAAN, KETIDAKPASTIAN DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN (Studi Kasus PT Chemco Harapan Nusantara Tahun 2015-2016) - Nikolas Bayu Radityo (Universitas Mercu Buana, 2016)
Abstract: The main objective of the development of Indonesia is in the field of human resources is to createquality human resources and prosperous Indonesia. This was done in view of the importance of improving thequality of human resources continues to change with the demands of each individual or group should be able toimprove its performance. The purpose of this study was to observe the effect of Power Distance, UncertaintyAvoidance and Leadership towards employee performance in PT. Chemco Harapan Nusantara. Especially inthe process of acquisition of the company by the German-Austrian organizational culture to Japan. Researchsamples are 86 respondents of PT. Chemco Harapan Nusantara in Karawang plant 3 is determined by thesampling method approach. Collecting data using questionnaires Engineering Research and Studies Library.Primary data processing using Quantitative Analysis Method. Discussion of the results obtained the followingconclusions: First, Multiple linear regression showed the results of Power Distance, Uncertainty Avoidance andLeadership 0.801 and 0.366. Based on the above data, it can be concluded that the leadership, have the greatestinfluence among other research variables, followed by Cultural Organization. Second, it can be concludedSimultaneous Test Results Power Distance, Uncertainty Avoidance and Leadership variables simultaneouslysignificant effect on employee performance in PT. Chemco Harapan Nusantara. Keywords: Power Distance, Uncertainty Avoidance, Leadership and Performance